Divergent Synthesis of Novel Cylindrocyclophanes that Inhibit Methicillin‐Resistant Staphylococcus aureus (MRSA). (12th June 2020) - Freudenreich, Julien J.; Bartlett, Sean; Robertson, Naomi S.; Kidd, Sarah L.; Forrest, Suzie; Sore, Hannah F.; Galloway, Warren R. J. D.; Welch, Martin; Spring, David R.
Abstract: The cylindrocyclophanes are a family of macrocyclic natural products reported to exhibit antibacterial activity. Little is known about the structural basis of this activity due to the challenges associated with their synthesis or isolation. We hypothesised that structural modification of the cylindrocyclophane scaffold could streamline their synthesis without significant loss of activity. Herein, we report a divergent synthesis of the cylindrocyclophane core enabling access to symmetrical macrocycles by means of a catalytic, domino cross‐metathesis‐ring‐closing metathesis cascade, followed by late‐stage diversification. Phenotypic screening identified several novel inhibitors of methicillin‐resistant Staphylococcus aureus . The most potent inhibitor has a unique tetrabrominated [7, 7]paracyclophane core with no known counterpart in nature. Together these illustrate the potential of divergent synthesis using catalysis and unbiased screening methods in modern antibacterial discovery. Abstract : Something new : The synthesis of novel cylindrocyclophanes varying in ring size, oxidation level and functionalisation is described. Key steps include a catalytic, domino cross‐metathesis‐ring‐closing metathesis cascade, and late‐stage diversification of the resulting resorcinol core. Antibacterial evaluation showed that the modifications are tolerated and we used this approach to identify several novel inhibitors of S. aureus and MRSA.